Densification mechanism of Ti-based metallic glass powders during spark plasma sintering process. (November 2015) - Liu, L.H.; Yang, C.; Yao, Y.G.; Wang, F.; Zhang, W.W.; Long, Y.; Li, Y.Y.
Abstract: Densification mechanism of Ti40.6 Zr9.4 Cu37.5 Ni9.4 Al3.1 metallic glass (MG) powder with different heating rates during spark plasma sintering process was investigated using annealed crystalline counterpart powder as the object of reference. Results show that compared with single-stage densification process in the whole sintering process for the annealed crystalline counterpart powder, MG powder contains a two-stage densification process. Meanwhile, higher heating rate promotes obviously densification behavior for the both kinds of alloy powders. Further densification mechanism analysis based on Frenkel model indicates that the activation energy of the viscous flow for MG powder in the supercooled liquid region decreases with increasing heating rate, thus promoting densification behavior of the MG powder in the first stage. In contrast, for the annealed crystalline counterpart powder, the promoting densification behavior with increasing heating rate is attributed to the higher temperature gradient between the sample center and the edge. The variation in the viscosity of melt-solidified Ti40.6 Zr9.4 Cu37.5 Ni9.4 Al3.1 bulk MG with temperature at different heating rates confirms the correctness of the obtained densification mechanism in our case. The results obtained can provide a new insight to understand the advantage of MG powder in fabrication of nano/ultrafine-grained titanium alloys with nearly full density. Highlights: MG powder has a two-stage densification process driven by viscosity change. Crystalline counterpart powder has single-stage densification one during sintering. Higher heating rate promotes obviously densification process for MG powder. Viscous flow activation energy for MG powder decrease with increasing heating rate.